Entre el compromiso y la huida - Alba Nubia Rodríguez Pizarro (Amnis)
In this article, three main questions are examined: Why do some women enter the political-military insurgent organizations in Colombia? Why do they stay in or quit these organizations? And eventually: what is permanent or changes in the practices and gender relations that occur in the insurgent groups, considering this evolution as functional to their organizational structures?